Zuhd and Minimalism in a Consumerist Society : Exploring Al-Ghazali and Fumio Sasaki's Thoughts - Syafiudin Kholiq Zaini; Ahmad Fadlun Nawal; Ahmad Maulidan Hidayat; Ilham Defriono (Pustaka Peradaban, 2023)
Zuhud and minimalism are popular ideas as alternatives to reduce the negative impact of a consumerist lifestyle. Abu Hamid Al-Ghazali, a well-known Islamic scholar, and Fumio Sasaki, a practitioner of modern minimalism, are two figures who represent ascetic and minimalist thoughts. This study aims to investigate the importance of zuhud practices and the art of minimalist living in the context of globalization and modernization by examining Abu Hamid Al-Ghazali and Fumio Sasaki. the research was conducted using a literature review by analyzing the works of Abu Hamid Al-Ghazali Fumio Sasaki. Through critical analysis, this study reveals the similarities and differences in their views on the practice of zuhud and the art of minimalist life. The results of the study show that the practice of zuhud and minimalism has significant relevance in globalization and modernization. Both emphasized the importance of reducing material possessions and finding happiness through simplicity. Abu Hamid Al-Ghazali emphasizes aspects of spirituality and relationship with God in the practice of zuhud, while Fumio Sasaki focuses more on freedom, inner peace, and happiness that is found through liberation from the burden of unnecessary things.